Treatment Patterns, Healthcare Utilization, and Related Costs for Prurigo Nodularis in Sweden - Laura von Kobyletzki; Alexandra Metsini; Simon E. Regnell; Michael Carlberg; Åke Svensson; Annarita Antelmi (Acta Dermato-Venereologica)
Prurigo nodularis (PN) is a chronic, itchy, inflammatory skin condition that negatively affects quality of life. A study was undertaken to investigate the healthcare utilization, including treatment patterns and direct costs for specialist care, for PN in Sweden. Linkage cohorts were created from national Swedish patient and prescription registers, and the cost-per-patient database of PN adults in specialist care in Sweden from 2015 to 2020. Around 875 patients were registered annually with a specialist diagnosis of PN in Sweden, with 3,548 specialist visits per year on average. In patients with severe PN with AD, the most common treatment sequence was topical treatment with corticosteroids followed by systemic prednisolone and methotrexate (32.6%). More than one-fifth of individuals with PN, and most with severe PN, had treatment for more than 1 year. For in- and outpatient care, the mean cost per visit was €458.6 and per patient per year around €1,862. The total annual cost of PN patients is estimated to be €1.6 million in Sweden. A high proportion of patients are treated for years with several, often systemic, treatment sequels. Targeted treatments for PN might improve patients’ quality of life and reduce the high related costs for the healthcare system.